Overview of Research Development on the Role of NF-κB Signaling in Mastitis - Muhammad Zahoor Khan (Animals, 2020)
Mastitis is the inflammation of the mammary gland. Escherichia coli and Staphylococcus aureus are the most common bacteria responsible for mastitis. When mammary epithelial cells are infected by microorganisms, this activates an inflammatory response. The bacterial infection is recognized by innate pattern recognition receptors (PRRs) in the mammary epithelial cells, with the help of Toll-like receptors (TLRs). Upon activation by lipopolysaccharides, a virulent agent of bacteria, the TLRs further trigger nuclear factor-κB (NF-κB) signaling to accelerate its pathogenesis. The NF-κB has an essential role in many biological processes, such as cell survival, immune response, inflammation and development. Therefore, the NF-κB signaling triggered by the TLRs then regulates the transcriptional expression of specific inflammatory mediators to initiate inflammation of the mammary epithelial cells. Thus, any aberrant regulation of NF-κB signaling may lead to many inflammatory diseases, including mastitis. Hence, the inhibiting of NF-κB signaling has potential therapeutic applications in mastitis control strategies. In this review, we highlighted the regulation and function of NF-κB signaling in mastitis. Furthermore, the role of NF-κB signaling for therapeutic purposes in mastitis control has been explored in the current review.